Analysis of pH Dose-dependent Growth of Sulfate-reducing Bacteria - Kushkevych, Ivan; Dordević, Dani; Vítězová, Monika (Open medicine (Warsaw, Poland), 2019)
Lower intraluminal colonic pH is an indication for the development of inflammatory bowel disease including active ulcerative colitis. Involvement of intestinal sulfate-reducing bacteria in decreasing bowel pH by the production of H2S and acetate as well as their sensitivity has never been reported before. The study of the relative pH and survival of Desulfovibrio piger Vib-7 by monitoring sulfate reduction parameters was the aim of this work. Monitoring was done through the measurement of bacterial growth (biomass), dissimilatory sulfate reduction parameters: sulfate consumption, lactate oxidation, hydrogen sulfide and acetate production. According to our results, we observed that lower pH (<5) significantly inhibited D. piger Vib-7 growth. This inhibition was also noticed when alkaline media (>9 pH) was used, though the reduction was not at the rate as in media with pH of 4. The research indicates that the growth of D. piger Vib-7 is inhibited at pH of 4 which is not as low as the pH found in people with severely developed inflammatory bowel diseases such as ulcerative colitis. Certainly the interaction (synergistic effect) between both hydrogen sulfide and acetate accumulation can also play an important etiological role in the development of bowel inflammation in humans and animals.
Keywords: Sulfate-reducing bacteria; pH gut; Toxicity; Hydrogen sulfide; Ulcerative colitis